PERBEDAAN PERAWATAN TALI PUSAT MENGGUNAKAN KASSA TOPIKAL ASI DENGAN KASSA KERING TERHADAP LAMA WAKTU PELEPASAN TALI PUSAT - Masjidah Masjidah; Mualimah Mualimah; Riska Riska (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2020)
Good cord care is an effort to prevent neonatal infection. There are various method of treatment used such a steril gauze, alcohol gauze 70%, povidone iodine (Betadine) 10%, and traditional treatments using honey, ghee oil (India), and breast milk. This study aims to find the difference umbilical cord treatments using breast milk topikal gauze and steril gauze in released times of cord in BPM NY”A” Sidoarjo. This was an experimental study with quASI experimental design. The population in this study was infants born during May until Juli at BPM NY”A”, as many as 20 respondents that comprised by 10 respondents with breast milk topical gauze and 10 respondents with an sterile gauze. The data sampling used puposive sampling technique by observation. The normality test used Shapiro-Wilk test and the statistical analyses used Mann Whitney test. The results of this study indicate that the longest of release time of infant's umbilical cord which wrapped by using an breast milk topikal indicate that the fastest release time is less than 5 days as many as 5 respondents (50%) and the normal release time (5-7 days) as many as 5 respondents (50%). The results of study by a sterile gauze is more than 7 days as many as 4 respondents (40%) and the normal released time (5-7 days) as many as respondents (60%). There is a difference between the release time between umbilical cord which wrapped by using sterile gauze and by having breast milk topical with p value of 0.003. The mothers of the respondents are suggested to choose open treatment as an effective treatment. For further researchers are expected to make direct observation to the other influencing faktors of the release time of the umbilical cord.